AVAILABILITY OF MINERAL ELEMENTS IN AN EXOTIC WEED ALTERNANTHERA TENELLA COLLA VAR. TENELLA VELDK - PATIL, RESHMA B; A Kore, Basavaraj (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objectives To study mineral status of an exotic weed Alternanthera tenella colla var. tenella veldk. Methods Mineral analysis in the leaves was carried out by acid digestion method as described by Toth et al. (1948). Sodium and potassium were estimated by flame photometer, Model-Elico, ch-22A. Remaining inorganic elements viz. calcium, potassium, magnesium, iron, manganese, zinc, copper, and cobalt were estimated by using Atomic Absorption Spectrophotometer, Perkin-Elmer, 3030 A. Result Potassium content of the leaves was high (4.11%) while nitrate content was very low (0.065%) with respect to major elements. In case of minor elements manganese is present at higher concentration (190.75 ppm) while molybdenum in very less quantity (0.10 ppm). Conclusion This study reveals that leaves of A. tenella var. tenella may be used as supplementary diet to human as well as livestock. Keywords: Alternanthera tenella var. tenella, Exotic weed, Invasive alien, Mineral elements.